Association between work stress and risk of suicidal ideation: A cohort study among Korean employees examining gender and age differences - Kim, Sun-Young; Shin, Young-Chul; Oh, Kang-Seob; Shin, Dong-Won; Lim, Weon-Jeong; Cho, Sung Joon; Jeon, Sang-Won (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVE ': 'The aim of this study was to identify work stress associated with the development of suicidal ideation with a focus on gender and age differences among Korean employees. ' ' METHODS ': 'The data of 95 356 healthy employees aged >18 years who had undergone at least two comprehensive health examinations at Kangbuk Samsung Hospital Health Screening Center, South Korea, were analyzed. Risk of suicidal ideation was assessed using a self-reported questionnaire examining suicidal ideation during the past year. Work stress was measured using the Korean Occupational Stress Scale-Short Form. A Cox proportional hazards model was used to examine relationship between work stress and suicidal ideation. Considering gender and age differences in the association between work stress and suicidal ideation, the data were stratified by gender and age groups. ' ' RESULTS ': 'During 289 706 person-years of follow-up, suicide ideation was identified in 3 460 participants. For male workers, high job demands and lack of reward were associated with the risk of suicidal ideation in young adults and midlife decade group. Job insecurity was associated with the risk of suicidal ideation in midlife decade and middle-aged and older adulthood. Organizational injustice was associated with the risk of suicidal ideation in middle-aged and older adulthood. Discomfort in an organizational climate was associated with the development of suicidal ideation in all age groups. For female workers, organizational injustice and discomfort in an organizational climate were associated with the risk of suicidal ideation in early adulthood. ' ' CONCLUSION ': 'The results suggested that certain work stressors are risk factors of suicidal ideation. Gender and age differences in components of work stress associated with suicidal ideation were also observed.
Keywords: age; age difference; cohort study; depression; effort–reward imbalance; gender; job control; job demand; job insecurity; job reward; KNHANES; Korea; Korea National Health and Nutrition Examination Survey; Korean employee; life span; mental health; organizational injustice; stress; suicidal ideation; suicide; work stress